Factors related to the intention of expatriates in business process outsourcing to work in Malaysia - Ahmad Irfan Fahmi, Al Qudsi (2022)
There are many factors that may influence individuals’ decision to work abroad. The purpose of this study is to investigate the factors that influence the intention of expatriates in business process outsourcing to work in Malaysia. In this research study, the researcher mainly focuses on the four factors which are high income, career prospects, quality of life, and family and friends’ influence. The primary data had been gathered by distributing questionnaires to the expatriates in BPO company with sample size of 382 respondents. Cronbach’s Alpha used to test the reliability of each variable. Pearson Correlation Coefficient and Multiple Linear Regression Analysis are used to examine the relationship between independent variables and dependent variable. The four independent variables showed a significant relationship towards expatriates’ intention to work in Malaysia. This research was concluded with the discussion of findings, implications of the study, limitations of the study and recommendation for future research.